Jalan Layang Paspati Sebagai Suatu Momentum Peremajaan Kota di Kawasan Tamansari Bandung - Sri Hidayati Djoeffan (The Institute for Research and Community Services, Institut Teknologi Bandung, 2001)
The area of Tamansari has a spesific historical background where the original function was for recreation and botanical garden. The growing number of population and its strategic location has changed the function of Tarnansari as high-density residential area, with a density of 535 persons/hectare (2000 figure). In relation with transportation problem is northern part of Bandung which is shown by traffic congestion in Siliwangi and Wastukencana roads, the government has designed a strategic development of fly-over which will pass the Tamansari area as an effort to solve the problem. This strategy is a good momentum for residential area redevelopment through redevelopment of Tamansari area